Isaiah the glory of the Messiah - Martin, Alfred, 1916-; Martin, John A. 1949- (Chicago, IL Moody Bible Institute, 1983)
Includes bibliographical references and index.
Keywords: Bible. O.T. Isaiah -- commentaries